Pengaruh Pemahaman Akuntansi Perpajakan Terhadap Hasil Belajar Mahasiswa Jurusan Akuntansi Universitas Muhammadiyah Metro Dengan Motivasi Belajar Sebagai Variabel Moderasi - Yashinta, Fadilah; Zanaria, Yulita; Septiani, Ana (Universitas Muhammadiyah Metro, 2024)
This research aims to determine the effect of understanding tax accounting on the learning outcomes of students majoring in accounting at Muhammadiyah Metro University with learning motivation as a moderating variable. The type of research used is quantitative research with a descriptive approach. The instrument used in this research is a questionnaire. Data analysis was carried out namely Moderated Regression Analysis (MRA). The research results show that Understanding Tax Accounting influences the learning outcomes of Accounting Department Students at Muhammadiyah Metro University. Learning motivation moderates the relationship between Understanding Tax Accounting and learning outcomes for students majoring in Accounting, Muhammadiyah Metro University